“We Are the Poles from Former Yugoslavia.” Transformation Processes Shifted in Time—The Biographical Perspective - Rozalia Ligus (Qualitative Sociology Review, 2019)
This paper is based on the first analysis of the 25 narrative interviews collected from March to November 2018 in small local communities in the Lower Silesia Region. All narrators belong to the families that were transferred from the former Yugoslavia in 1946 to the western lands which were incorporated to Poland. The socio-cultural conditions are significant for local development, so I present some features of localism after 1989 when the state transformation processes started. Next, I discuss the narrators’ self-identity dilemmas and make an attempt to conceptualize “migrating biography” as one of the features of living in a postmodern world.